2015
DOI: 10.1155/2015/947450
|View full text |Cite
|
Sign up to set email alerts
|

Morel-Lavallée Lesion: Report of a Case of Unknown Mechanism

Abstract: Morel-Lavallée lesions are cystic lesions occurring between the subcutaneous tissue and the underlying layer of a fascia. The most frequent mechanism of occurrence is posttraumatic, usually after degloving injuries. The chain of events leading to the occurrence of this lesion is the formation of a potential space between the subcutaneous tissue and the firmly attached deep fascia, which in turn fills with blood and/or lymph and/or necrotic fat, secondary to disruption of the capillaries. We present a case of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…To this end, surgical debridement with resection of the pseudocapsule is a more definitive treatment option. 5,12 We believe that endoscopic approach is better than open approach in prevention of post-operative wound complication. However, endoscopic approach still has the risk of inadequate debridement to prevent recurrence and risk of spreading of the bacteria to the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, surgical debridement with resection of the pseudocapsule is a more definitive treatment option. 5,12 We believe that endoscopic approach is better than open approach in prevention of post-operative wound complication. However, endoscopic approach still has the risk of inadequate debridement to prevent recurrence and risk of spreading of the bacteria to the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was fortunate enough to have not sustained skeletal injuries, despite being involved in a high kinetic trauma. Kontis et al reported a case of a 74-year-oldmale patient with a cystic lesion of the lateral surface of the left thigh in which a meticulous history acquisition failed to ascertain an alleged mechanism of injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Prompt treatment is paramount as neglected cases may get infected and lead to extensive skin necrosis. Also delay in treatment leads to formation of pseudocapsule, making complete resolution difficult 8 . Conservative management is most effective in cases presenting early.…”
Section: Introductionmentioning
confidence: 99%